Constructing hierarchical structure via in situ growth of CNT in SiO2-coated carbon foam for high-performance EMI shielding application. (3rd May 2022) - Huang, Ben; Yue, Jianling; Fan, Benhui; Tang, Xiu-Zhi; Liu, Yu; Huang, Xiaozhong
Abstract: Carbonated melamine foam (CMF) with a three-dimensional (3D) inner connected network is considered as one of the promising candidates to fabricate electromagnetic interference (EMI) shielding materials. To further improve EMI shielding performance, CMF based hybrids with three-dimensional structure by the combination of SiO2 and in-situ growth carbon nanotubes (CNT) have been synthesized for preparing polydimethylsiloxane (PDMS) composite: CMF@SiO2 -CNT/PDMS. Owing to the structural match between the length of CNT and the diameter of holes in the CMF@SiO2, the relatively high electrical conductivity of 50.43 S/m has been achieved in the composite with the thickness of 2 mm, which assures an excellent EMI shielding effectiveness (SET  = 61.34 dB) in the frequency range from 8.2 to 12.4 GHz. Meanwhile, a high absorption effectiveness (SEA  = 53.65 dB) of the composite infers an absorption dominant performance of the composite because of the unique porous structure and inter-connected conductive network, which helps to avoid secondary EMI pollution. We hope this work can provide a new route for fabricating EMI shielding materials with high performance. Graphical abstract: Image 1